Mariia Dmytrivna Kultaieva as a scientific supervisor - Володимир Абашнік (Філософія освіти)
Words of gratitude and deep respect for Mariia Dmytrivna Kultaieva from her colleague and student Volodymyr Oleksiyovych Abashnik.